Straight-to-test colonoscopy: Has it improved the detection of colorectal cancer? A 7- year review. Issue 5 (October 2021) - Thanapal, Mohana Raj; Thin, Noel; Alagaratnam, Swethan; Walshe, Maria; Parmar, Chetan; Bhan, Chetan; Mukhtar, Hasan
Abstract: Aim: Early diagnosis of colorectal cancer (CRC) improves outcome. Straight-To-Test (STT) pathway was introduced in Whittington Hospital in 2012. The aim was to reduce the time to first oncological treatment and minimise unnecessary outpatient clinic appointments. However, this pathway has added significant burden to the trust in terms of number of procedures to be done.We assessed the diagnostic yield and the effectiveness of this pathway in improving the time to diagnosis of colorectal cancer. We also performed a cost-effective analysis and discussed the current literature along with interventions to further improve the benefits of STT investigations. Method: This is a prospectively collected data of all patients who underwent STT examinations in a single centre from January 2012 till December 2018. The parameters collected were patient details, procedures performed, findings and discharge plan. We also performed a cost-effective analysis. Results: A total 1648 (90.8%) of patients identified suitable for STT pathway underwent colonoscopy or flexible sigmoidoscopy. From this, 764 (50.2%) patients had diagnosed pathology and CRC was detected in 50(3%) of the patients. We also estimated annual savings of £ 21, 599.54 (£151, 196.76 in seven years). Patients on the STT pathway took 25 days to obtain results as compared to 40 days in the standard pathway. The decision to take the patient off the cancer pathway was shortened by 3 weeks. Conclusion: STT pathway has proven to be safe and cost-effective means of investigation. However, further improvement is needed in the implementation to make it a sustainable. mode of investigation in long run and increase the pickup rate of colorectal cancer through STT. Highlights: Colorectal cancer detection rate in STT pathway was 3.0%. More than 50% had pathological findings from the endoscopic procedure. Average of 15 days faster in completing STT pathway compared to standard pathway. STT pathway accounted for a saving around £151, 196.76 in seven years.